Windows 10 simplified step by step instructions for easy learning - McFedries, Paul (Visual, a Wiley brand, 2015)
Fully updated to cover Windows 10, this highly visual, plain-English guide covers all the new features in addition to the basics, giving you a one-stop resource for complete Windows 10 mastery